Pemantauan DJJ dengan Bantuan Dopler pada Ibu Hamil Ny. “H” umur 22 tahun G1P0A0 Sejak Usia Kehamilan 31 minggu 4 Hari Secara Komprehensif - Arini, Arini; Nurasmi, Nurasmi; hutagaol, Iin octaviana (UKInstitute, 2024)
The infant mortality rate in Indonesia reaches 35 per 1000 live births, while neonatal mortality (0-28 days) is 19 per 1000 live births. These figures are much higher compared to neighboring countries. The aim of this study is to provide comprehensive midwifery care by utilizing a Doppler device to monitor the fetal heart rate (FHR) in a pregnant woman, Mrs.